2014
DOI: 10.1002/jcla.21732
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–Lymphocyte Ratio in Patients With Familial Mediterranean Fever

Abstract: Our results demonstrate that N/L ratio is higher in patients with active FMF compared with FMF patients in remission and controls, and a cut-off value of 2.63 can be used to identify patients with active FMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 16 publications
(26 reference statements)
1
25
0
2
Order By: Relevance
“…22,23 Moreover, NLR and MPV had higher levels at the attack periods in familial Mediterranean fever patients. 24,25 High levels of MPV and NLR have been found as a predictor for gastrointestinal bleeding in the Henoch-Schonlein purpura. 26,27 Decreased MPV and NLR have been shown with the treatment of rheumatoid arthritis and ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Moreover, NLR and MPV had higher levels at the attack periods in familial Mediterranean fever patients. 24,25 High levels of MPV and NLR have been found as a predictor for gastrointestinal bleeding in the Henoch-Schonlein purpura. 26,27 Decreased MPV and NLR have been shown with the treatment of rheumatoid arthritis and ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the N/L ratio was higher in active FMF than in remission as well as control patients (19). However, they did not find any relationship between active and attack-free periods in terms of WBC counts.…”
Section: Discussionmentioning
confidence: 90%
“…In current study, WBC counts were higher only in patients with compound mutations. In addition, Celikbilek et al (19) reported that the N/L ratio was significantly higher in patients with FMF-related amyloidosis than in patients without FMF-related amyloidosis. Amyloidosis is an important cause of morbidity and mortality in patients with FMF (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations